A variable-rate modulation and coding scheme for low earth orbit satellites - Butchart, Kevin Robert (Department of Electrical Engineering, 2016)
Low Earth Orbit (LEO) satellites are increasingly being used for a wide variety of communications applications. These satellites have to operate in widely varying channel conditions. These conditions are often significantly better than the 'worst case' situations that are experienced and thus a single rate transmission scheme is clearly suboptimal. The objective of the thesis is to suggest and test a method of modulation/coding that can take advantage of better signal strength conditions in order to improve data transmission rates. In order to provide the goal of approximately 50kbps transmission in a 10kHz Frequency Division Multiple Access (FDMA) channel it was necessary to consider spectrally efficient, rather than power efficient, modulations. The proposed modulation scheme makes use of an eight-dimensional trellis coded modulation system. Multiple signal constellation sets are used in conjunction with this coding in order to provide different transmission rates, depending on the signal to noise ratio and the channel state. To enhance the suitability of the modulation scheme for the channel, it was combined with Reed-Solomon Coding and interleaving in an inner/outer code arrangement. Various means of determining when to switch between coding rates were discussed briefly, but an in-depth treatment of the subject fell outside of the scope of the thesis. Various combinations of these codes were tested in gaussian noise conditions and various degrees of Rician and Rayleigh fading. In order to make use of the higher rate QAM constellations, it was necessary to provide the decoder with channel state information. The tested system achieved its purpose of providing a variable rate coding scheme resulting in good performance over a range of channel conditions. It is fairly flexible and can be adapted to specific channel requirements.